Preservation, ancient manuscripts, knowledge management - Sukaesih, Sukaesih; Winoto, Yunus; Rusmana, Agus; Kurniasih, Nuning (Record and Library Journal, 2016)
Garut is one district in West Java province which has the potential of cultural heritage which is very interesting. One of the cultural heritage in Garut which is be the site of ancient manuscripts (manuscripts). Relating to the existence of ancient manuscripts in Garut regency of the many ancient texts only a small portion that has been recorded and stored in the museum, while most have not been registered again and was saved by members of the public. To keep this heritage alive and useful for future generations hence the need for awareness of all members of society and this is one of the efforts in building knowledge management. The main purpose of knowledge management is to encourage sustainability knowledge within an organization or society, so expected that knowledge will not stop the people who have the knowledge, but can be accessed and studied by others who need them. In this research method used is the method mix (mix method) with pengum-gathering techniques of data in the form of questionnaires, interviews, observation and through the study of literature. The results showed that of most members of the community that holds the codex in preserving ancient manuscripts which are still done simply by storing in a clean and dry at certain times to clean dust and dirt on the manuscript. Regarding the awareness of community members who have an ancient manuscript codex to report ownership to the government in general remains low, This is because of concerns that they have ancient manuscripts must be submitted to the government.